Insect Hormones - Nijhout, H. Frederik (Princeton University Press, 1994)
Although insect endocrinology is one of the oldest and most active branches of insect physiology, its classic general texts are long out of date, while its abundant primary literature provides little biological context in which to make sense of the discipline as a whole. In this book, H. Frederik Nijhout's goal is to provide a complete, concise, and up-to-date source for students and nonspecialists seeking an overview of the dynamic and wide-ranging science that insect endocrinology has become since its beginnings nearly eighty years ago in the study of insect metamorphosis. The author offers a comprehensive survey of the many roles that hormones play in the biology of insects. Among the topics discussed are the control of molting, metamorphosis, reproduction, caste determination in social insects, diapause, migration, carbohydrate and lipid metabolism, diuresis, and behavior. The account features a summary of the most current and accurate thinking on the complex roles of ecdysone and juvenile hormone in the control of metamorphosis, a process still misunderstood and misrepresented in biological textbooks and many professional reviews. Throughout, the book's emphasis is on the biology of the organism and the ways in which physiological and developmental regulatory mechanisms are integrated into the insect's life cycle.